One-pot synthesis of ethylenediamine-connected graphene/carbon nanotube composite material for isolation of clenbuterol from pork. (1st September 2017) - Yuan, Yanan; Jiao, Xiaoyan; Han, Yehong; Bai, Ligai; Liu, Haiyan; Qiao, Fengxia; Yan, Hongyuan
Highlights: A simple and time-saving one-pot synthesis for preparation of EGC is developed. EGC possess a three-dimensional framework structure for avoiding agglomeration. EGC is successfully used for isolation and determination of clenbuterol in pork. Good extraction and purification efficiency over other adsorbents. Abstract: A fluffy porous ethylenediamine-connected graphene/carbon nanotube composite (EGC), prepared by a simple and time-saving one-pot synthesis, was successfully applied as an adsorbent in pipette-tip solid-phase extraction (PT-SPE) for the rapid extraction and determination of clenbuterol (CLB) from pork. In the one-pot synthesis, carbon nanotubes were inserted into graphene sheets and then connected with ethylenediamine through chemical modification to form a three-dimensional framework structure to prevent agglomeration of the graphene sheets. Under the optimum conditions for extraction and determination, good linearity was achieved for CLB in the range of 15.0–1000.0 ng g −1 ( r = 0.9998) and the recoveries at three spiked levels were in the range of 92.2–96.2% with relative standard deviation ≤9.2% ( n = 3). In comparison with other adsorbents, including silica, NH2, C18, and Al2 O3, EGC showed higher extraction and purification efficiency for CLB from pork samples. This analytical method combines excellent adsorption performance of EGC and high extraction efficiency of PT-SPE.